Tube erosions following glaucoma drainage device implantations - Julia Prinz; Karl Mercieca; Laura-Jill Förster; Kira Hilmers; Peter Walter; Matthias Fuest; Björn Bachmann; Claus Cursiefen; Verena Prokosch (Scientific Reports)
Abstract Glaucoma drainage devices (GDD) are an important treatment option for advanced and complex glaucoma patients. To prevent tube erosion, different materials may be used to patch the tube. The aim of this study was to compare tube erosion rates of allogenous fascia lata versus corneal stromal patches relating to Ahmed glaucoma implant (AGI) and Paul glaucoma implant (PGI) surgeries. In this retrospective study, 84 patients were included. The tube was covered with allogenous fascia lata (n = 43) or a corneal stromal patch (n = 41). 32 eyes of 31 patients underwent AGI and 52 eyes of 52 patients underwent PGI surgeries. The number of tube erosions was evaluated during 18 months of follow-up. Tube erosions occurred in 4 patients with fascia lata patches (9.3%) and 1 patient (2.4%) with a corneal stromal patch (p = 0.184). In the superior quadrants (n = 78; 92.9% of all GDD), tube erosions were significantly more frequent with fascia lata (n = 4) compared to corneal stromal (n = 0) patches (p = 0.045). There was no difference in the number of tube erosions between the AGI (n = 2) and PGI (n = 3) group (p = 0.928). Tube erosions after GDD are rare. Fascia lata patches were more frequently associated with tube erosions than corneal stromal patches.